Experimental Study of the Conditions for Quenching Forest Combustible Materials; Journal of Engineering Physics and Thermophysics; Vol. 90, iss. 3 - Antonov D. V. Dmitry Vladimirovich; Volkov R. S. Roman Sergeevich; Zhdanova A. O. Alena Olegovna; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2017, 2017)
Title screen